Cutthroat dogs [large type] - Estleman, Loren D. (Estleman, Loren D. Amos Walker novels., 2022)
"Someone is dead who shouldn't be, and the wrong man is in prison." Nearly twenty years ago, college freshman April Goss was found dead in her bathtub, an apparent suicide, but suspicion soon fell on her boyfriend. Dan Corbeil was convicted of her murder and sent to prison. Case closed. Or is it?"--